The "Afghan issue" within the framework of the Shanghai Cooperation Organization - Birimkulova, Г.У.; Zhomart, Н.Ж. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2024)
The article will focus on the "Afghan issue", which has a very important geostrategic role within the framework of the Shanghai Cooperation Organization. In order to understand the problem more deeply, first we are talking about historical facts that explain the internal state of Afghanistan. Among them there will be a talk about the war with the USSR, the civil war inside the country and the wars against the united group of foreign troops. It tells about the return to power of the Taliban group. In addition, it is noted what changes took place in the country when the Taliban came to power. Importance is attached to changing the balance of power in the region. That is, we are talking about the competition of states creating a new influence on Afghanistan, freed from the United States. It will tell about the initiatives and projects implemented between the Member States and the new authorities of Afghanistan. The main importance is attached to agreements with the Central Asian States. By the end of the article, we will talk about the Samarkand SCO Summit. In addition, signed agreements will be listed. Finally, a conclusion is made by combining all the collected material.